2003
DOI: 10.1046/j.1538-7836.2003.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet functional defects in women with unexplained menorrhagia

Abstract: Summary. Menorrhagia is a common clinical problem and is unexplained in more than 50% of women. Although studies suggest that von Willebrand's Disease (VWD) is found in a substantial number of women with unexplained menorrhagia, the prevalence of platelet defects in women with menorrhagia is unknown. To determine the prevalence of platelet and other hemostatic defects, we evaluated women ages 17-55 diagnosed with unexplained menorrhagia. Seventy-four women (52 white, 16 black, six other) were studied. Bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
160
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 29 publications
14
160
0
3
Order By: Relevance
“…Menorrhagia is a valuable predictor of a bleeding disorder in women. The frequency of vWD in women with menorrhagia ranges from 5% to 20% in different studies [10][11][12][13][14][15] (Table I). The different prevalences reported may reflect the different study populations (population based or referral), variable definitions of menorrhagia and vWD, timing, types of laboratory tests, and requirements for retesting.…”
Section: Frequency Of Vwd In Women With Menorrhagiamentioning
confidence: 99%
See 2 more Smart Citations
“…Menorrhagia is a valuable predictor of a bleeding disorder in women. The frequency of vWD in women with menorrhagia ranges from 5% to 20% in different studies [10][11][12][13][14][15] (Table I). The different prevalences reported may reflect the different study populations (population based or referral), variable definitions of menorrhagia and vWD, timing, types of laboratory tests, and requirements for retesting.…”
Section: Frequency Of Vwd In Women With Menorrhagiamentioning
confidence: 99%
“…The criteria for diagnosis and frequency and timing of testing varied among the published studies (Table I). Studies requiring testing on only one occasion may underestimate the prevalence of vWD due to the normal fluctuation in vWF levels [11,13,14]. The three studies of women with objectively confirmed menorrhagia required testing on multiple occasions [10,12,15].…”
Section: Frequency Of Vwd In Women With Menorrhagiamentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet dysfunction has been reported as the most prevalent bleeding disorder among women with menorrhagia, with von Willebrand disease being the second most prevalent (13%) [103,104].…”
Section: The Haemostatic System During the Menstrual Cyclementioning
confidence: 99%
“…27 Platelet disorders and factor deficiencies are less common but have also been identified in women with menorrhagia. 26,28,29 Therefore IBDs should be borne in mind when investigating women with menorrhagia.…”
Section: Menorrhagia and Ibdsmentioning
confidence: 99%